Feminism in Sarah Polley’s Drama Women Talking - Syamsul Bahri; Nurdelia Nasution; Salsah Br. Nainggolan; Reva Angelina (Educational Dynamics: International Journal of Education and Social Sciences, 2025)
The drama Woman Talking has many feminist values can be found, especially about gender equality, women’s freedom, and moving away from patriarchy. The values shown in this film are already being practiced today, where women and men are seen as equals in terms of rights and opportunities. These important ideas inspire writers to explore them more deeply, aiming to raise awareness among men so they do not look down on women. This study aims to examine the representation of feminism in Women Talking, a drama directed by Sarah Polley. Using a qualitative descriptive approach, this research analyzes the film’s narrative and dialogue to explore how the women fight for bodily autonomy, voice, and the freedom to choose their own paths. The results indicate that Women Talking has five of six types of feminism theory, which the liberal feminism is the largest one with 39%, and then radical feminism 32%, traditional marxist feminism 16%, socialist feminism 12%, and the last is postmodern feminism 6%. This drama has no dialog that talking about critical race feminisim. The findings show that Women Talking is not only a space for the expression of voices long silenced, but also a quiet yet powerful form of collective resistance against systemic oppression.